Pedagogical Strategies for Teaching Rhythmic Gymnastics in Primary Education: A Systematic Review - Br Tarigan, Gita Nurgaya; Ramadan, Ramadan; Estes, Celestina (Journal of Foundational Learning and Child Development, 2025)
Purpose of the study: This systematic review examines pedagogical strategies employed in teaching rhythmic gymnastics to primary education students (ages 6-12 years), analyzing their effectiveness, implementation methods, and impact on motor skill development, creativity, and student engagement. Materials and methods: A comprehensive search was conducted across PubMed, Scopus, Web of Science, ERIC, and SPORTDiscus databases from inception to December 2024. Studies were included if they: (1) focused on rhythmic gymnastics instruction in primary education, (2) described specific pedagogical strategies, (3) employed empirical research designs, and (4) were published in peer-reviewed journals. Data extraction followed PRISMA guidelines, with quality assessment performed using the Mixed Methods Appraisal Tool (MMAT) and the Physiotherapy Evidence Database (PEDro) scale. Results: Twenty-seven studies met inclusion criteria, encompassing 2,847 primary school children across 12 countries. Five primary pedagogical approaches emerged: game-based learning (n=11, 40.7%), creative teaching methods (n=8, 29.6%), task-oriented instruction (n=5, 18.5%), cooperative learning (n=2, 7.4%), and technology-enhanced pedagogy (n=1, 3.7%). Game-based learning demonstrated significant improvements in motor coordination (d=0.82, p<0.001), student motivation (d=0.76, p<0.01), and rhythmic competency (d=0.68, p<0.01). Creative teaching methods showed particular efficacy in developing artistic expression and cognitive flexibility. Conclusions: Evidence supports game-based and creative pedagogical strategies as effective approaches for teaching rhythmic gymnastics in primary education. These methods enhance motor development while maintaining high levels of student engagement and enjoyment. Future research should investigate long-term retention effects and optimal strategy combinations for diverse learner populations